Moderating effect of gender on the relationships between extension worker availability, individual factors and empowerment among members of self-help groups in North-Eastern Nigeria - Yakubu, Sani Gombe (2017)
This study was designed to determine the moderating effect of gender in the relationship between extension worker availability, individual factors (participation and volunteerism) and empowerment among members of self-help groups in North-Eastern Nigeria. Specifically, the objectives of the study were to; 1) determine the level of empowerment among the SHG members in North-Eastern Nigeria, 2) determine the level of extension worker availability, participation and volunteerism among the SHG members in North-Eastern Nigeria, 3) determine the relationship between extension worker availability, participation and volunteerism among the SHG members in North-Eastern Nigeria, 4) determine the overall contribution of extension worker availability, participation and volunteerism on empowerment of SHG members in North-Eastern Nigeria, and 5) determine the moderating effect of gender on the relationships between extension worker availability, participation, volunteerism variables with empowerment among the SHG members in North-Eastern Nigeria.